(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
At A Time When The United Nations And Other International Organizations Have Stressed On A Number Of Occasions The Idea Of The Interdependence Of Human Rights And The Need To Be Enjoyed By Them In Full Swing, The Arab League At The Beginning Of Its Inception Has Not Paid Much Attention To Human Rights. Even A Reference In The Preamble To Human Rights, In View Of The Historical Circumstances That Have Emerged In The Arab League. However, Over The Next Years, This Latter Began To Address This Issue In Line With The Developments In The International Community In The Field Of Human Rights. It First Established The Arab Permanent Committee On Human Rights, Which Prepared The Arab Charter On Human Rights, Which Ensured The Inclusion Of Economic Rights By Its Content. A Mechanism To Follow Up Its Implementation Is The Arab Human Rights Committee, To Be The Establishment Of An Arab Court Of Human Rights Within The Framework Of The League Of Arab States As A Second Control System. Key Words- The Arab Human Rights System, The Protection Of Economic Rights, The Arab Permanent Committee On Human Rights, The Arab Human Rights Committee , The Arab Court Of Human.